2020
DOI: 10.5194/gmd-2020-302
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SPEAD 1.0 – A model for Simulating Plankton Evolution with Adaptive Dynamics in a two-trait continuous fitness landscape applied to the Sargasso Sea

Abstract: Abstract. Diversity plays a key role in the adaptive capacities of marine ecosystems to environmental changes. However, modeling phytoplankton trait diversity remains challenging due to the strength of the competitive exclusion of sub-optimal phenotypes. Trait diffusion (TD) is a recently developed approach to sustain diversity in plankton models by allowing the evolution of functional traits at ecological timescales. In this study, we present a model for Simulating Plankton Evolution with Adaptive Dynamics (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…This, however, comes at the cost that diversification into multiple peaks cannot be easily incorporated as opposed to our approach here. Finally, our moment equations closely resemble those derived in trait-diffusion approaches (Merico et al, 2014;Le gland et al, 2020), where mutations are generated by a diffusion process in trait space. Merico et al (2014) derived the moment equations for well-mixed, single-species, single-trait populations and Le gland et al ( 2020) extended this to multiple traits and spatial structure by way of reaction-diffusion equations in continuous space.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This, however, comes at the cost that diversification into multiple peaks cannot be easily incorporated as opposed to our approach here. Finally, our moment equations closely resemble those derived in trait-diffusion approaches (Merico et al, 2014;Le gland et al, 2020), where mutations are generated by a diffusion process in trait space. Merico et al (2014) derived the moment equations for well-mixed, single-species, single-trait populations and Le gland et al ( 2020) extended this to multiple traits and spatial structure by way of reaction-diffusion equations in continuous space.…”
Section: Discussionmentioning
confidence: 61%
“…We shall refer to these types of equations as trait-space equations. As in adaptive dynamics and trait-diffusion approaches (Merico et al, 2014;Le gland et al, 2020;Nordbotten et al, 2020), we are not here concerned with any specific genetic makeup that would result in these dynamics for phenotypic traits, but simply assume that new heritable variation is generated in some ecological process such as births and mutations. For a single class, our setup is however very similar to the one-locus continuum-of-alleles class of models (Kimura, 1965;Bürger, 1986).…”
Section: Generic Class-structured Model and Moment Equations For Fixe...mentioning
confidence: 99%
“…Finally, our moment equations closely resemble those derived in trait-diffusion approaches (Merico et al, 2014; Le gland et al, 2020), where mutations are generated by a diffusion process in trait space. Merico et al (2014) derived the moment equations for well-mixed, single-species, single-trait populations and Le gland et al (2020) extended this to multiple traits and spatial structure by way of reaction-diffusion equations in continuous space. For mutation kernels with small variance-covariance matrices without covariances, our mutation convolution integral is well approximated by such trait-diffusion processes (Kimura, 1965; Débarre et al, 2013), and our assembly framework is easily adapted to this setting, equipping the trait-diffusion approaches with a way of assembling eco-evolutionarily stable communities of several species.…”
Section: Discussionmentioning
confidence: 57%
“…In a phytoplankton model Peeters and Straile (2018) compared trait-space equations without mutations to single-species moment equations, and concluded that single-species moment equations failed to provide any useful information when considering parts of parameter space where the trait-space equations diverged into multiple species. In a similar model using the trait-diffusion approach Le gland et al (2020) noted that their trait-space equations sometimes exhibited multi-modality and speculated on the utility of modeling multiple modes, making the selection of how many modes to include based on functional groups. While multi-species moment models are not new (Sasaki and Dieckmann, 2011; Norberg et al, 2012; Barabás and D’Andrea, 2016), our assembly approach obviates the need for a-priori decisions on how many modes or species to include by assembling the correct number of species, at least as long as the number of species is not ambiguous.…”
Section: Discussionmentioning
confidence: 99%